The complete mitogenome of Nomia chalybeata (Hymenoptera: Halictidae) and phylogenetic analysis - Hongying Li; Huanhuan Lu; Shigui Huang; Xiaodong Fan; Ancai Luo; Dunyuan Huang (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitogenome of Nomia chalybeata was sequenced. The mitochondrial length of N. chalybeata was 16,692 bp (AT content 85.4%), with 37 classic invertebrate mitochondrial genes (including 13 protein-coding genes, 22 transporter RNAs, and two ribosomal RNAs) and AT-rich region (AT content 91.7%). The maximum-likelihood phylogenetic relationship was constructed using 11 species from Hymenoptera. Through the phylogenetic relationship, our research team successfully used the molecular data of the mitochondrial genome to verify that N. chalybeata belongs to the family Halictidae, and also provides molecular data for the database of the family Halictidae.